Ovine Leukocyte Microparticles Generated by the CentriMag Ventricular Assist Device In Vitro. Issue 6 (7th March 2018) - Pieper, Ina Laura; Radley, Gemma; Christen, Abigail; Ali, Sabrina; Bodger, Owen; Thornton, Catherine A.
Abstract: Ventricular assist devices (VADs) are a life‐saving form of mechanical circulatory support in heart failure patients. However, VADs have not yet reached their full potential due to the associated side effects (thrombosis, bleeding, infection) related to the activation and damage of blood cells and proteins caused by mechanical stress and foreign materials. Studies of the effects of VADs on leukocytes are limited, yet leukocyte activation and damage including microparticle generation can influence both thrombosis and infection rates. Therefore, the aim was to develop a multicolor flow cytometry assessment of leukocyte microparticles (LMPs) using ovine blood and the CentriMag VAD as a model for shear stress. Ovine blood was pumped for 6 h in the CentriMag and regular samples analyzed for hemolysis, complete blood counts and LMP by flow cytometry during three different pump operating conditions ( low flow, standard, high speed ). The high speed condition caused significant increases in plasma‐free hemoglobin; decreases in total leukocytes, granulocytes, monocytes, and platelets; increases in CD45 + LMPs as well as two novel LMP populations: CD11b bright /HLA‐DR − and CD11b dull /HLA‐DR +, both of which were CD14 − /CD21 − . CD11b bright /HLA‐DR − LMPs appeared to respond to an increase in shear magnitude whereas the CD11b dull /HLA‐DR + LMPs significantly increased in all pumping conditions. We propose that these two populations are released from granulocytes and T cells, respectively, but further research is needed to better characterize these two populations.